Functional redundancy and compensation: Deletion of multiple murine Crisp genes reveals their essential role for male fertility. Issue 12 (10th October 2020) - Curci, L.; Brukman, N. G.; Weigel Muñoz, M.; Rojo, D.; Carvajal, G.; Sulzyk, V.; Gonzalez, S. N.; Rubinstein, M.; Da Ros, V. G.; Cuasnicú, P. S.
Abstract: Mammalian Cysteine‐RIch Secretory Protein (CRISP) family includes four members present in sperm and reported to regulate Ca 2+ channels and fertilization. Based on our previous observations using single knockouts models and suggesting the existence of functional compensation among CRISP proteins, we investigated their relevance for male fertility by generating multiple Crisp gene mutants by CRISPR/Cas9 technology. Whereas targeting of Crisp1 and Crisp3 yielded subfertile males with early embryo developmental defects, the same deletion in zygotes from fertile Crisp2 −/− .Crisp4 −/− mice led to the generation of both triple and quadruple knockout mice exhibiting a complete or severe disruption of male fertility due to a combination of sperm transport, fertilization, and embryo developmental defects linked to intracellular Ca 2+ dysregulation. These observations reveal that CRISP proteins are essential for male fertility and organize in functional modules that contribute distinctly to fertility success, bringing insights into the mechanisms underlying functional redundancy/compensation in protein families and emphasizing the importance of generating multiple and not just single knockout which might be masking the true functional relevance of family genes.